Endocrine abnormalities in lithium toxicity - Shanks, Gabriella (Clin Med (Lond), 2017)
Lithium toxicity can manifest as a variety of biochemical abnormalities. This case report describes a patient presenting to the emergency department with neuropsychiatric symptoms on a background of bipolar disorder, for which she was prescribed lithium for 26 years previously. Cases of lithium toxicity are rare but can be severe and this case report demonstrates to clinicians that they must be thorough in investigating patients with lithium toxicity, as there are many potential abnormalities that can manifest concurrently.